A qualitative exploration of the influence of social media on South African parents - Moonsamy, Alisha (The IIE, 2020)
Social media has gained popularity among parents in recent years, as either a form of entertainment or communication with other individuals. Use of social media has also shown to have influence’s on parenting; causing parental distraction, acting as a supportive community for parents, a way to help parents fulfil their household needs, and overall influencing the way parents’ parent. Findings from the conducted interviews indicated that social media does influence parents, with the relationship between social media usage aiding in more positive influences than negative. Findings provided insightful data to fill in the gap of literature pertaining to South African parents use of social media in a manner that facilitates positive influences and minimises negatives, such as monitoring time spent on social media. Further studies may be conducted in the future expanding on recommendations for South African parents.
Keywords: Social media; Influence; Parents; South Africa